The Effect of Deep Breathing Relaxation Techniques on Reducing Dysmenorrhea Pain in Adolescent Girls at The Indah Dormitory in Cemani Village - Mustain, Mustain; M.C, Shela; Tri, Yuniarti; Witriani, Witriani; Hussein, Mahjana (LPPM Universitas Duta Bangsa Surakarta, 2024)
Menstrual pain (Dysmenorrhea) is pain in the lower abdomen that spreads to the waist and thighs that is felt before and after menstruation. Dysmenorrhea can be experienced by women who have higher intrauterine pressure and have twice the prostaglandin levels than women who do not experience dysmenorrhea. In the world, the incidence of desmenorrhea exceeds 50%. Meanwhile in Indonesia, it is estimated that 55% of productive women experience dysmenorrhea which interferes with their activities. Dysmenorrhea pain can be treated with non-pharmacological therapy, one of which is deep breathing relaxation techniques. The aim of this research was to determine the effect of deep breathing relaxation techniques on reducing dysmenorrhea pain in adolescent girls at the Indah Dormitory in Cemani Village, Sukoharjo Regency. This research uses a quasi-experimental approach with a one group pre-test and post-test design approach. The research sample was 60 young female respondents with sampling using random sampling techniques. The results showed that there was a significant reduction in pain levels in the intervention group after the deep breathing relaxation technique was carried out. The average reduction in pain in the intervention group was 2.5 points on the VAS scale, while the control group only experienced a reduction of 0.5 points. The statistical test results showed a significant difference (p < 0.05) between the intervention group and the control group, indicating that the deep breathing relaxation technique was effective in reducing dysmenorrhea pain. Beautiful Cemani Village. It is hoped that young women can perform deep breathing relaxation techniques correctly when experiencing pain due to dysmenorrhea.